Răspuns :
[tex]( \frac{7}{3} - \frac{4}{3} ) - \frac{12}{13} [/tex]
[tex] = \frac{7 - 4}{3} - \frac{12}{13} [/tex]
[tex] = \frac{3}{3} - \frac{12}{13} [/tex]
[tex] = 1 - \frac{12}{13} [/tex]
[tex] = \frac{13}{13} - \frac{12}{13} [/tex]
[tex] = \frac{13 - 12}{13} [/tex]
[tex] = \frac{1}{13} [/tex]
[tex]( \frac{5}{6} + \frac{7}{6} ) - \frac{1}{7} [/tex]
[tex] = \frac{5 + 7}{6} - \frac{1}{7} [/tex]
[tex] = \frac{12}{6} - \frac{1}{7} [/tex]
[tex] = 2 - \frac{1}{7} [/tex]
[tex] = \frac{14}{7} - \frac{1}{7} [/tex]
[tex] = \frac{14 - 1}{7} [/tex]
[tex] = \frac{13}{7} [/tex]
[tex] \frac{4}{3} - ( \frac{9}{11} + \frac{2}{11} )[/tex]
[tex] = \frac{4}{3} - \frac{9 + 2}{11} [/tex]
[tex] = \frac{4}{3} - \frac{11}{11} [/tex]
[tex] = \frac{4}{3} - 1[/tex]
[tex] = \frac{4}{3} - \frac{3}{3} [/tex]
[tex] = \frac{4 - 3}{3} [/tex]
[tex] = \frac{1}{3} [/tex]
[tex] = \frac{7 - 4}{3} - \frac{12}{13} [/tex]
[tex] = \frac{3}{3} - \frac{12}{13} [/tex]
[tex] = 1 - \frac{12}{13} [/tex]
[tex] = \frac{13}{13} - \frac{12}{13} [/tex]
[tex] = \frac{13 - 12}{13} [/tex]
[tex] = \frac{1}{13} [/tex]
[tex]( \frac{5}{6} + \frac{7}{6} ) - \frac{1}{7} [/tex]
[tex] = \frac{5 + 7}{6} - \frac{1}{7} [/tex]
[tex] = \frac{12}{6} - \frac{1}{7} [/tex]
[tex] = 2 - \frac{1}{7} [/tex]
[tex] = \frac{14}{7} - \frac{1}{7} [/tex]
[tex] = \frac{14 - 1}{7} [/tex]
[tex] = \frac{13}{7} [/tex]
[tex] \frac{4}{3} - ( \frac{9}{11} + \frac{2}{11} )[/tex]
[tex] = \frac{4}{3} - \frac{9 + 2}{11} [/tex]
[tex] = \frac{4}{3} - \frac{11}{11} [/tex]
[tex] = \frac{4}{3} - 1[/tex]
[tex] = \frac{4}{3} - \frac{3}{3} [/tex]
[tex] = \frac{4 - 3}{3} [/tex]
[tex] = \frac{1}{3} [/tex]